2015
DOI: 10.1038/ng0815-962b
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: Transcriptional regulator PRDM12 is essential for human pain perception

Abstract: In the version of this article initially published, there was an error with the affiliations for author Roman Chrast. His correct affiliations are:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Notably, our findings are also supported by a recent clinical report that reveals that PRDM12 (a member of the PRDI-BF1 and RIZ homology domain-containing family) is essential for human perception of pain, as pathogenic mutations cause a congenital loss of pain perception in humans. 40 This clinical finding further indicates that the PRDI-BF1 and RIZ homology domain-containing family may play a role in pain perception and provides clinical support for our study.…”
Section: Pain Medicinesupporting
confidence: 78%
“…Notably, our findings are also supported by a recent clinical report that reveals that PRDM12 (a member of the PRDI-BF1 and RIZ homology domain-containing family) is essential for human perception of pain, as pathogenic mutations cause a congenital loss of pain perception in humans. 40 This clinical finding further indicates that the PRDI-BF1 and RIZ homology domain-containing family may play a role in pain perception and provides clinical support for our study.…”
Section: Pain Medicinesupporting
confidence: 78%
“…At the root of the TrkA-lineage, from which emerge most if not all small diameter somatosensory neurons (i.e, nociceptors and C-LTMR), stands the histone methyltransferase (HMT) related transcriptional regulator Prdm12. In the recent years, several studies have shown how much Prdm12 is instrumental in the emergence of the TrkA-lineage, which fails to develop in its absence [10][11][12][13]15]. Mechanistically, Prdm12 appears to act as a pseudo methyltransferase as it has been shown to interact with G9a when overexpress in HEK29T3 cells and to increase H3K9me2 level when overexpressed in Xenopus neuralized animal cap explants [15,22].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, several studies have shown how much Prdm12 is instrumental in the emergence of the TrkA-lineage, which fails to develop in its absence [10][11][12][13]15]. Mechanistically, Prdm12 appears to act as a pseudo methyltransferase as it has been shown to interact with G9a when overexpress in HEK29T3 cells and to increase H3K9me2 level when overexpressed in Xenopus neuralized animal cap explants [15,22]. However, the in vivo relevance of G9a for Prdm12 functions in the emergence of the nociceptive lineage during somatosensory neurogenesis has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations